Neuroprotective effect of β-asarone against Alzheimer’s disease: regulation of synaptic plasticity by increased expression of SYP and GluR1 - Liu SJ; Yang C; Zhang Y; Su RY; Chen JL; Jiao MM; Chen HF; Zheng N; Luo S; Chen YB; Quan SJ; Wang Q (Dove Medical Press, 2016)
Si-jun Liu,1,* Cong Yang,2,* Yue Zhang,2,* Ru-yu Su,2 Jun-li Chen,2 Meng-meng Jiao,2 Hui-fang Chen,2 Na Zheng,2 Si Luo,2 Yun-bo Chen,2 Shi-jian Quan,1 Qi Wang21School of Chinese Materia Medica, 2Institute of Clinical Pharmacology, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China*These authors contributed equally to this workAim: β-asarone, an active component of Acori graminei rhizome, has been reported to have neuroprotective effects in Alzheimer’s disease. As the underlying mechanism is not known, we investigated the neuroprotective effects of β-asarone in an APP/PS1 double transgenic mouse model and in NG108 cells.Materials and methods: APPswe/PS1dE9 double transgenic male mice were randomly assigned to a model group, β-asarone treatment groups (21.2, 42.4, or 84.8 mg/kg/d), or donepezil treatment group (2 mg/kg/d). Donepezil treatment was a positive control, and background- and age-matched wild-type B6 mice were an external control group. β-asarone (95.6% purity) was dissolved in 0.8% Tween 80 and administered by gavage once daily for 2.5 months. Control and model animals received an equal volume of vehicle. After 2.5 months of treatment, behavior of all animals was evaluated in a Morris water maze. Expression of synaptophysin (SYP) and glutamatergic receptor 1 (G1uR1) in the hippocampus and cortex of the double transgenic mice was assayed by Western blotting. The antagonistic effects of β-asarone against amyloid-β peptide (Aβ) were investigated in vitro in the NG108-15 cell line. After 24 hours of incubation, cells were treated with 10 µm Aβ with or without β-asarone at different concentrations (6.25, 12.5, or 25 µM) for an additional 36 hours. The cytotoxicity of β-asarone was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay of cell viability, and cell morphology was evaluated by bright-field microscopy after 24 hours of treatment. The expression of SYP and GluR1 in cells was detected by Western blot assay in the hippocampus and brain cortex tissues of mice.Results: β-asarone at a high dose reduced escape latency and upregulated SYP and GluR1 expression at both medium and high doses. Cell morphology evaluation showed that β-asarone treatment did not result in obvious cell surface spots and cytoplasmic granularity. β-asarone had a dose-dependent effect on cell proliferation.Conclusion: β-asarone antagonized the Aβ neurotoxicity in vivo, improved the learning and memory ability of APP/PS1 mice, and increased the expression of SYP and GluR1 both in vivo and in vitro. Thus, β-asarone may be a potential drug for the treatment of Alzheimer’s disease.Keywords: neuroprotective effect, β-asarone, synaptic plasticity, synaptophysin, glutamatergic receptor 1